PENGEMBANGAN APLIKASI GEOMETRY OF MATHEMATICS (GEOMATHICS) DENGAN METODE GAMIFIKASI UNTUK MENGATASI LEARNING LOSS PASCA PANDEMI - Sephia Rahayu Purnama; Sekar Wulan Dari; Slamet Muhammad Ilham; Lina Kristianti; Tamara Jasmine Prasetyani; Aan Nurfahrudianto (LPPM Universitas Kahuripan Kediri, 2022)
This study originaled from students problems who identificated a learning loss during Pandemic COVID-19. Starting that problem there is a need for a learning media that can be used by students to reduce the danger of learning loss. This research was conducted with R&D approach (Research and Development), which produces a learning media by adapting the method of ADDIE.. The purpose of this research is to create an android application-based learning media, namely Geometry of Mathematics (GEOMATHICS) to overcome Learning Loss with the gamification method. The results obtained from the validation indicate that the GEOMATHICS application has met the eligibility criteria for learning media obtained from the validation results with the results of the assessment being 80% from material experts, 90% from media experts and 94% from practicing experts. With the results obtained the average assessment of learning media is 88%, which is included in the very good category and does not need to be revised. Therefore, the results of data analysis obtained have answered the problem formulation, namely the GEOMATHICS application has met the eligibility criteria to be applied in the learning process at SMP Plus Rahmat Kediri.